APLIKASI SISTEM MONITORING GAS NO2 DAN CO BERBASIS IOT - Muhammad Nur Fauzi; Bagus Fatkhurrozi; Deria Pravitasari (JURNAL ELEKTROSISTA, 2023)
Clean air quality plays an important role in maintaining the health of living things and climate change. Significant exposure to dirty air results in premature aging, lung cancer, especially exposure to carbon monoxide (CO) and nitrogen dioxide (NO2) gases. Increasing air pollution requires solutions to reduce the impact of air pollution. The first solution is air quality monitoring. The thingspeak platform air quality monitoring has channel ID restrictions. Based on these problems, this research focuses on updating using an open source platform that does not have channel ID restrictions. In this study, an IoT-based NO2 and CO Gas Monitoring Application was designed. QOS test results obtained packet loss reached a distance of 120m and throughput obtained in the bad category at LOS. The distance of the transmitter and receiver affects throughput and packet loss. The results of the application have no channel restrictions, gas notifications are detected and dangerous gas works, and the color of the circular progress bar can indicate the gas category.